Identifikasi Keadaan Sifat Fisik dan Kimia Tanah pada Tanaman Cengkeh di Desa Tincep dan Kolongan Atas Kecamatan Sonder - Dotulong, Jacky R.G.; Kumolontang, Wiesje J.N.; Kaunang, Djoni; Rondonuwu, Jenny J. (Universitas Sam Ratulangi, 2015)
Abstract This study aimed to identify the state of physical and chemical properties of the soil on the Cloves plant in the village of Tincep and Kolongan Atas Subdistrict Sonder. This study conducted using a survey method with their implementation as follows: the soil samples were taken at two locations is overgrown Cloves plant with good growth rates and less well, each location was taken four soil samples, two soil samples were taken at Cloves plant with good growth rates and another two soil samples were taken on Cloves plant with less well growth rates. Soil sampling conducted by digging a minipit with size 50 x 50 x 50 cm were taken at the canopy boundary of Cloves plant and the soil samples were taken top layer (horizon A) and lower layers (horizon B) which is based on the effect of organic matter on the soil layer (A and B). The parameters observed was physical properties of soil that is, texture, structure, and consistency; and chemical properties of soil that is, nitrogen total, phosphor available, potassium available, c-organic, and pH. The results showed clove plants with good growth and less well the specified visually not affected by the state of chemical of soil, but is influenced by physical properties of soil, because on the Cloves plant which less well grow on the horizon B was found weathered material. Keywords: Cloves, Physical and Chemical properties of soil, Growth, Weathered material